Nuovi testi su ceramica da Cuma eolica. Dipinti, graffiti, ostraka - Claudio Biagetti (Pallas, 2017)
This paper focuses on twelve new texts on ceramic shards coming from the site of Aeolic Cyme. The evidence consists of painted texts and graffiti, ranging between the third century BC and the sixth or seventh century CE. Interestingly, one of the painted texts contains a possible reference to a local civic tribe named Cadmeis.